COMMUNITY PARTICIPATION IN MANGROVE FOREST MANAGEMENT IN MOJO VILLAGE, ULUJAMI DISTRICT, PEMALANG REGENCY - Aprilia Fitri P; Ardiana Yuli Puspitasari; Eppy Yuliani (International Conference on Coastal and Delta Areas, 2015)
Mangrove forest in Mojo Village, Ulujami District, Pemalang Regency has an area used for nature tourism in coastal areas which provide protection the macro climate balance in Pemalang. The Regulation No.3/2011 about Pemalang Spatial Planning Year 2011-2031 have been discussing the mangrove forest development. Management of Mangrove forest in Mojo villages empowering by the local communities through farmer groups in cooperation with Local Governments and Institutions that called OISCA (The Organization for Industrial, Spiritual and Cultural Advancement-International). The research problem is want to know the forms of community involvement in the management of mangrove forests in Mojo Village.This research was conducted with the aim of measuring the level of community participation in the management of mangrove forest in the Mojo village, District Ulujami, Pemalang City through 3 Arnsteinsâ€™ variables of participation with 8 indicators ranging from levels manipulation to citizen power. The methodology used is mixed methods (quantitative and qualitative) with descriptive methods through rationalistic approach and logical deductive thinking.The result is level of community participation in the management of Mojo villagesâ€™ mangrove forest located on the 6th floor of participation stair, it is partnership with the lowest level and still under the influence of the 5th participation â€œPlacationâ€. Mojoâ€™s community activities still relies on Government dan OISCA funding. There are no improvement of initiative and willingness to develop activities independently.Keywords: Participation, Management, Forest, Mangrove